Production of theophylline via aerobic fermentation of pu-erh tea using tea-derived fungi - Zhou, Binxing (BMC Microbiol, 2019)
BACKGROUND: Caffeine is one of the most abundant methylxanthines in tea, and it remains stable in processing of general teas. In the secondary metabolism of microorganism, theophylline is the main conversion product in caffeine catabolism through demethylation. Microorganisms, involved in the solid-state fermentation of pu-erh tea, have a certain impact on caffeine level. Inoculating an appropriate starter strain that is able to convert caffeine to theophylline would be an alternative way to obtain theophylline in tea. The purpose of this study was to isolate and identify the effective strain converting caffeine to theophylline in pu-erh tea, and discuss the optimal conditions for theophylline production. RESULTS: Caffeine content was decreased significantly (p < 0.05) and theophylline content was increased significantly (p < 0.05) during the aerobic fermentation of pu-erh tea. Five dominant fungi were isolated from the aerobic fermentation and identified as Aspergillus niger, Aspergillus sydowii, Aspergillus pallidofulvus, Aspergillus sesamicola and Penicillium mangini, respectively. Especially, A. pallidofulvus, A. sesamicola and P. mangini were detected in pu-erh tea for the first time. All isolates except A. sydowii TET-2, enhanced caffeine content and had no significant influence on theophylline content. In the aerobic fermentation of A. sydowii TET-2, 28.8 mg/g of caffeine was degraded, 93.18% of degraded caffeine was converted to theophylline, and 24.60 mg/g of theophylline was produced. A. sydowii PET-2 could convert caffeine to theophylline significantly, and had application potential in the production of theophylline. The optimum conditions of theophylline production in the aerobic fermentation were 1) initial moisture content of 35% (w/w), 2) inoculation quantity of 8%, and 3) incubation temperature at 35 °C. CONCLUSIONS: For the first time, we find that A. sydowii PET-2 could convert caffeine to theophylline, and has the potential value in theophylline production through aerobic fermentation.